Use of Lentiviral Particles As a Cell Membrane-Based mFasL Delivery System for In Vivo Treatment of Inflammatory Arthritis - Rodríguez-Frade, José M.; Guedán, Anabel; Lucas, Pilar; Martínez-Muñoz, Laura; Villares, Ricardo; Criado, Gabriel; Balomenos, Dimitri; Reyburn, Hugh T.; Mellado, Mario (Frontiers in Immunology, 2017)
During budding, lentiviral particles (LVP) incorporate cell membrane proteins in the viral envelope. We explored the possibility of harnessing this process to generate LVP expressing membrane proteins of therapeutic interest and studied the potential of these tools to treat different pathologies. Fas-mediated apoptosis is central to the maintenance of T cell homeostasis and prevention of autoimmune processes. We prepared LVP that express murine FasL on their surface. Our data indicate that mFasL-bearing LVP induce caspase 3 and 9 processing, cytochrome C release and significantly more cell death than control LVP in vitro. This cytotoxicity is blocked by the caspase inhibitor Z-VAD. Analysis of the application of these reagents for the treatment of inflammatory arthritis in vivo suggests that FasL-expressing LVP could be useful for therapy in autoimmune diseases such as rheumatoid arthritis, where there is an excess of Fas-expressing activated T cells in the joint. LVP could be a vehicle not only for mFasL but also for other membrane-bound proteins that maintain their native conformation and might mediate biological activities.